Decisions, Decisions: Review of Mindware: Tools for Smart Thinking by Richard E. Nisbett - Anne Kelly (Numeracy, 2019)
Richard Nisbett. 2015. Mindware: Tools for Smart Thinking. (New York, NY: Farrar, Strauss, and Giroux). 336 pp. ISBN: 9780374536244. Social psychologist Richard E. Nisbett provides help in identifying and overcoming faulty cognitive strategies and replacing them with more accurate heuristics. To do so, Nisbett draws from statistics, correlation, experiments, differences in Western and Eastern thought, and, especially, social influence.